A ‘Governance Network Model’ for legally democratic National Sports Bodies (NBS) in Malaysia / Jady Z. Hassim ... [et al.] - Z. Hassim, Jady; M. Ali, Hasani; H. Hassan, Kamal; M.A.R. Merican, Rooshida; Y, Haniwarda; A.W. Roslan, Wan Syazana; W. Salman, Nadhratul; M. Shapie, Mohamad Nizam (2014)
The good governance practices for sport bodies in the world concerns more on the exercise of power within an organizational system. The system emphasizes the principle of transparency, accountability, democracy, responsibility, equity, efficiency and effectiveness. If all these principles ceased to exist, the system will collapse. The Malaysian system of sports governance is still based on two models of ‘hierarchical pyramid network’ and ‘democratic anchorage’ respectively. These two models are undemocratically accepted and denying some of the principles of good governance. As a result, the stakeholders (players, supporters, unions and government) perceived both as the main failure to establish good sports governance practices. Thus, to establish good governance practices for sports bodies in Malaysia, this article analyses the new ‘governance network model’. It also examines on how the new model interacts efficiently and able to develop good governance practices for sport bodies. To achieve this, the research adopted qualitative and quantitative approaches. The constitutional policy of national sports bodies (NSB) was legally analysed. The clauses in the sports constitution are surveyed using Rasch Modelling Techniques. The survey highlighted the low monitoring compliance of the existing NSB for the purpose of current changes of sports legislations and industrial environments. The findings also showed that despite of commercialisation and industrialisation of sports, the NSB cannot guarantee the same in term of adopting good governance practices. The article recommended the changes of environment from autonomous self-governance to mixed governance (governance network model). This will guarantee the good governance practices for sport bodies in Malaysia.